On Arguments from Ignorance - Hinton, Martin David (Informal Logic, 2018)
The purpose of this paper is twofold: to give a good account of the argument from ignorance, with a presumptive argumentation scheme, and to raise issues on the work of Walton, the nature of abduction and the concept of epistemic closure. First, I offer a brief disambiguation of how the terms 'argument from ignorance' and 'argumentum ad ignorantiam' are used. Second, I show how attempts to embellish this form of reasoning by Douglas Walton and A.J. Kreider have been unnecessary and unhelpful. Lastly, I offer a full and effective account of the argument from ignorance and discuss the lessons of the analysis.